Pengaruh Lingkungan Kerja Fisik, Disiplin Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada Pabrik Gula Merah UD Bunga Mas - Mochamad Puguh Andriyanto; Edi Murdiyanto; Agung Pambudi Maha Putra (Populer: Jurnal Penelitian Mahasiswa, 2023)
This research aims to determine the influence of the physical work environment, work discipline and work stress on employee performance at the UD Bunga Mas brown sugar factory. The variables used in this research are Physical Work Environment (X1), Work Discipline (X2), Work Stress (X3), and Employee Performance (Y). The research location is the UD Bunga Mas Brown Sugar Factory which is located in Karanglo Hamlet, Tales Village RT 01 RW 04 Ngadiluwih District, Kediri Regency. By using data collection techniques in the form of interviews, questionnaires and observations.Meanwhile, the analysis used uses quantitative methods with multiple linear regression tools using the SPSS version 25.0 software program. Based on tests carried out by partial linear regression analysis, it shows that the Physical Work Environment (X1) has a negative and insignificant effect on Employee Performance (Y) and Work Discipline (X2) has a positive and insignificant effect on Employee Performance (Y). Meanwhile, the Job Stress variable (X3) has a negative and significant influence on Employee Performance (Y). This shows a significant value for variable X1 0.116 > 0.05, variable X2 0.538 > 0.05, and X3 0.000 < 0.05. Partially, the Physical Work Environment (X1), Work Discipline (X2), and Work Stress (X3) have a positive and significant effect on Employee Performance (Y) at the UD Bunga Mas Brown Sugar Factory.